FAMOUS PEOPLE MODEL ON STUDENTS’ ACHIEVEMENT IN WRITING - Sumar sih; Rahmad Husein; Nora Ronita Dewi (BAHAS, 2017)
The objective of this study was to find out whether  using Famous People Model in writing descriptive  can improve students’ achievement in writing descritive text. It was conducted by using experimental research. The population of consisted of 4 classes. Two classes were taken as the sample by using random sampling technique. The class X-1 was as experimental group and X-2 was as the control group. The experimental group was taught by using Famous People Model, otherwise control group was taught by using conventional technique. The instrument for collecting data was writing test. The data were analyzed by using t-test formula. The result shows that Famous People Model has a significant effect on students achievement in writing descriptive text. The result shows that the t-observed is higher than t-table (3.102 > 2.024 (α-0.05)) with the degree of freedom (n) = 20. Therefore,Famous People Model significantly affects on the students’ ability in writing descriptive text.